Statin therapy in patients with acute coronary syndrome: Low-density lipoprotein cholesterol goal attainment and effect of statin potency - Chinwong,D. (Dove Medical Press Ltd., 2015)
© 2015 Chinwong et al. Background: Elevated low-density lipoprotein cholesterol (LDL-C) is associated with an increased risk of coronary artery disease. Current guidelines recommend an LDL-C target of <70 mg/dL (< 1.8 mmol/L) for acute coronary syndrome (ACS) patients, and the first-line treatment to lower lipids is statin therapy. Despite current guidelines and the efficacious k'pid-lowering agents available, about half of patients at very high risk, including ACS patients, fail to achieve their LDL-C goal. This study assessed LDL-C goal attainment according to use of high and low potency statins in routine practice in Thailand. Methods: A retrospective cohort study was performed by retrieving data from medical records and the electronic hospital database for a tertiary care hospital in Thailand between 2009 and 2011. Included were ACS patients treated with statins at baseline and with follow-up of LDL-C levels. Patients were divided into high or low potency statin users, and the proportion reaching the LDL-C goal of <70 mg/dL was determined. A Cox proportional hazard model was applied to determine the relationship between statin potency and LDL-C goal attainment. Propensity score adjustment was used to control for confounding by indication. Results: Of 396 ACS patients (60% males, mean age 64.3+11.6 years), 229 (58%) were treated with high potency statins and 167 (42%) with low potency statins. A quarter reached their target LDL-C goal (25% for patients on high potency statins and 23% on low potency statins). High potency statins were not associated with increased LDL-C goal attainment (adjusted hazards ratio 1.22, 95% confidence interval 0.79-1.88; P=0.363). Conclusion: There was no significant effect of high potency statins on LDL-C goal attainment. Moreover, this study showed low LDL-C goal attainment for patients on either low or high potency statins. The reasons for the low LDL-C goal attainment rate warrants further investigation.